Evaluation of rice (Oryza sativa L.) genotypes for low phosphorus stress tolerance - Roy, Maitry; Khatun, Sheikh Mahfuja; Hassan, Lutful; Hossain, Mohammad Anwar (Journal of Plant Stress Physiology, 2023)
Phosphorus (P) deficiency is a prime factor limiting rice growth and yield around the globe. Understanding how plants respond to P starvation is very important for breeding varieties with enhanced P uptake and use efficiency. To assess the effect of low P stress on yield and yield contributing traits, an experiment was conducted using six rice genotypes applying two treatments (optimum and deficient P conditions). Data on yield and yield attributing traits viz., days to first flowering (DFF), days to maturity (DM), plant height (PH), number of total tillers/plant (NTTP), number of effective tillers/plant (NETP), panicle length (PL), 100-seed weight (100-SW) and yield per plant (YPP) were recorded. Analysis of variance showed highly significant variation among the genotypes (G), treatments (T) and G × T interaction. When compared with control, a significant reduction in yield and yield attributing traits was observed in most of the studied genotypes in response to low P stress. The highest reduction in YPP was recorded in BRRI dhan78 whereas the lowest reduction was observed in Binadhan-17. Principal component analysis revealed that the first three principal components explained 85.2% of the total variation. Yield per plant (g) showed significant positive correlation with PH, PL, NTTP and NETP whereas it showed significant negative correlation with DFF, DM and 100-SW. Based on stress tolerance indices Binadhan-17, BRRI dhan71 and BRRI dhan79 were categorized as tolerant genotypes and selected for cultivation in P deficient areas and are recommended for the genetic improvement of low P stress tolerance in rice.